2008
DOI: 10.1038/nbt1379
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the mosaic structure of trans-acyltransferase polyketide synthases for natural product discovery and pathway dissection

Abstract: Modular polyketide synthases (PKSs) are giant bacterial enzymes that synthesize many polyketides of therapeutic value. In contrast to PKSs that provide acyltransferase (AT) activities in cis, trans-AT PKSs lack integrated AT domains and exhibit unusual enzymatic features with poorly understood functions in polyketide assembly. This has retarded insight into the assembly of products such as mupirocin, leinamycin and bryostatin 1. We show that trans-AT PKSs evolved in a fundamentally different fashion from cis-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
429
1
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 376 publications
(457 citation statements)
references
References 48 publications
19
429
1
8
Order By: Relevance
“…1B; SI Appendix, Table S3). Although trans-AT PKS systems have been found in a wide range of bacteria (16,17), none have been reported for cyanobacteria, which are otherwise rich sources of cis-AT PKSs (17,18). These observations suggested the possibility of metabolic products that might be novel, not only from structural but also from ecological and evolutionary perspectives.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…1B; SI Appendix, Table S3). Although trans-AT PKS systems have been found in a wide range of bacteria (16,17), none have been reported for cyanobacteria, which are otherwise rich sources of cis-AT PKSs (17,18). These observations suggested the possibility of metabolic products that might be novel, not only from structural but also from ecological and evolutionary perspectives.…”
Section: Resultsmentioning
confidence: 94%
“…This observation indicated that a large part of the polyketide product would resemble pederin and onnamides. The remainder of the core structure was more difficult to predict, because two of the four KSs (KS6 and KS8) fell into clades consisting of KS 0 s, which are nonelongating KS variants that usually show little consistency between phylogeny and substrate structure (16). KS 0 6 was positioned in a small subclade containing homologs from the rhizoxin and bacillaene PKSs that are involved in shifting double bonds from the α,β-to the β,γ-position (24,25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of the thailandamides (Fig. 1, 5), a family of polyenes comprising multiple geometric isomers generated by the tha gene cluster (25,26), was increased 8-36-fold, depending on the isomer (Fig. 4A).…”
Section: 1909 [M+h]mentioning
confidence: 99%
“…Blastp searches of the dual-function PksJ-KR revealed numerous orthologs predominantly in trans-AT clusters, including those responsible for mupirocin, bryostatin, and rhizoxin biosynthesis (19,20), with 44%, 44%, and 43% sequence identity, respectively. Notably, many of these possible dual-function ␣/␤ KRs are predicted to act on C 2 -extended ␣-ketoacyl-Gly-S-T thioesters, perhaps reflecting a preference for conformationally flexible substrates (21). For example, the first KR domain in Ta1 from the myxovirescin biosynthetic cluster is 38% identical to PksJ-KR.…”
Section: Discussionmentioning
confidence: 99%